Government Effectiveness and Socio-Economic Equity: An Empirical Analysis of Sustainable Social Protection Systems in Developing Countries Using Two-Step System GMM Econometric Approach - Ahmad, Umar Suffian; Fakher, Muhammad Amjad; Arif, Muhammad (Pakistan Languages and Humanities Review, 2024)
This paper aims to study the nexus between government effectiveness and socioeconomic equity, which leads to a sustainable social protection system. We have empirically investigated the nexus through a panel data set of 46 developing countries for a period of 20 years. Developing countries face socio-economic inequity due to ineffective government policies leads to the collapse of the social protection system. We have developed an index of sustainable protection systems using the Keyser Meyer Olkin Methodology used as a sampling adequacy. We found a positive association between government effectiveness and social protection systems in developing countries. However, a weak mechanism may cause the poor implementation of sustainable social protection needs utmost policy maneuvers in those countries. There is a need for capacity building of government institutions to improve their effectiveness. Action should be taken that promotes transparency, accountability, and good governance practices.